Does Observed Conflict Recovery Play a Role in Adolescent Dating Aggression?. (20th June 2022) - Lorber, Michael F.; Slep, Amy M. S.; Heyman, Richard E.; Tiberio, Stacey S.; Damewood, Gabriella N.; Mitnick, Danielle M.; Bruzzese, Jean‐Marie
Abstract : In a study of conflict recovery and adolescent dating aggression, 14‐ to 18‐year‐old couples ( N  = 209 dyads) participated in a 1‐hr observational assessment. Negative behavior was observed during conflict‐evoking "hot" tasks and in a "cooldown" task. Physical and psychological dating aggression were assessed via questionnaires. Negative behavior measured in the cooldown task was not associated with dating aggression after controlling for carryover effects of negativity from the hot to cooldown tasks. Moreover, cooldown negativity moderated the associations of hot task negativity and dating aggression. Actor and partner effects were disentangled via dyadic data analyses. Given the paucity of observational studies of dating aggression, our findings are an important contribution to the literature and in need of replication and extension.